TINJAUAN GEOLOGIS GEMPA CIANJUR NOVEMBER 2022 - Lolom Evalita Hutabarat (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2023)
The earthquake that struck Cianjur Regency, West Java Province, on Monday, November 21, 2022, at 1.21 pm, killed 268 people and damaged or destroyed over 2,000 buildings (BMKG, 2022). The soil movement is generally in rock layers class C (hard soil) to layer D (medium soil), according to the geological map of building damage below. The Cugenang fault, which runs north 347°E and tilts 82.8° to the right perpendicular from Nagrak village to Ciherang village to the northeast in the Cianjur region, is the cause of severe building damage. Ground movements generally occur in rock layers C (hard soil) to D (medium soil). Because the earthquake's magnitude was not too large, the faults did not continue to the surface (surface rupture). However, they caused many aftershocks of lower intensity in the direction of Warungkondang to Karang Tengah for 12 km and a width of 8 km. The Rupture Area was the worst location for building damage. Even though the earthquake movement begins at the epicenter, the epicenter is not always the location of the most severe damage. The fault line of the earthquake source points to the West-South-West (WSW)-East Northeast (ENE) with the fault slope (dip) to the south and the fault direction to the left, according to data on the distribution of the epicenter of the earthquake. As a preventative measure, a technical review of the geological aspects of the Cianjur earthquake is required to ensure no casualties or material loss at the exact location if repeated earthquakes occur